2021
DOI: 10.1002/ehf2.13254
|View full text |Cite
|
Sign up to set email alerts
|

The impact of frailty according to Clinical Frailty Scale on clinical outcome in patients with heart failure

Abstract: Aims There is currently no gold standard in evaluating frailty in patients with heart failure (HF), and the prognostic value of frailty according to the Canadian Study of Health and Aging Clinical Frailty Scale (CFS) on mortality in patients with HF is still unknown. Methods and results Among consecutive 596 patients after their discharge from HF in Kokura Memorial Hospital (Kitakyushu, Japan) during 2015, their frailty at discharge was assessed according to CFS. Patients were classified into three groups: low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 31 publications
(59 reference statements)
1
15
0
3
Order By: Relevance
“…Previous studies have demonstrated that frailty is common in patients with HF and is associated with mortality (29,30). The CFS is a semi-quantitative tool for evaluating patients' frailty and has been widely used because of its simplicity and usefulness (31). Our study demonstrated that the CFS is an independent prognostic factor for HF in elderly patients.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies have demonstrated that frailty is common in patients with HF and is associated with mortality (29,30). The CFS is a semi-quantitative tool for evaluating patients' frailty and has been widely used because of its simplicity and usefulness (31). Our study demonstrated that the CFS is an independent prognostic factor for HF in elderly patients.…”
Section: Discussionsupporting
confidence: 56%
“…Of interest, markers of cachexia such as low albumin and haemoglobin were also associated with late mortality independent of age and sex. Interestingly, frailty, malnutrition, and cachexia often co‐exist in older individuals; in a recent study examining more than 110 000 older individuals across the UK, frailty was detected in >90% of patients characterized by malnutrition and in 100% of patients characterized by cachexia, 21 while recent studies suggest an inverse relationship between CFS and albumin or BMI 22 . The association of CFS with various tissue loss syndromes (sarcopenia, frailty, cachexia, and malnutrition) as a general marker of baseline patient status is worth exploring in future studies regarding COVID‐19 patients and older individuals in general.…”
Section: Discussionmentioning
confidence: 99%
“…Low albumin concentration is a factor of bad prognosis in HF is connected with malnourishment and FS [45,46]. This parameter could be considered as an alternate one for CholT in our model; however, in the analysis, CholT had a better predicting value compared to albumin.…”
Section: Discussionmentioning
confidence: 89%